Boosting Potassium Storage Performance of the Cu2S Anode via Morphology Engineering and Electrolyte Chemistry - Peng, Qingkui; Zhang, Shipeng; Yang, Hai; Sheng, Binbin; Xu, Rui; Wang, Qingsong; Yu, Yan (ACS nano, 2020)
Transition metal sulfides (TMSs) have been demonstrated as attractive anodes for potassium-ion batteries (KIBs) due to the high capacity, abundant resource, and excellent redox reversibility. Unfortunately, practical implementation of TMSs to KIBs is still hindered by the unsatisfactory cyclability and rate performance which result from the vast volume variation during charge/discharge processes. Herein, a uniform nitrogen-doped carbon coated Cu2S hollow nanocube (Cu2S@NC) is designed as an anode material for the KIB, which displays an outstanding cycle performance (317 mAh g–1 after 1200 cycles at 1 A g–1) and excellent rate capacity (257 mAh g–1 at 6 A g–1) in a half-cell. The hollow nanosized structure can both shorten the diffusion length of potassium ions/electrons and buffer the volume expansion upon cycling. Besides, the high concentration electrolyte is beneficial to form the stable solid electrolyte interphase (SEI) film, reducing the interface impedance and enhancing the cycling stability. Ex situ transmission electron microscopy (TEM) and ex situ X-ray diffraction (XRD) reveal the reaction mechanism of Cu2S@NC.